Analyses of energy transfer of Cr3+ and Nd3+ co-doped Y3Al5O12 ceramic powders at the 4T1 level of Cr3+ ion excitation. (3rd February 2022) - Honda, Yoshiyuki; Motokoshi, Shinji; Jitsuno, Takahisa; Fujioka, Kana; Yamada, Toshihiro; Yoshida, Minoru
Abstract: The concentration dependence of energy transfer from Cr 3+ to Nd 3+ at the 4 T 1 level excitation in Nd/Cr:YAG was investigated by the fluorescence decay curves of Cr 3+ and Nd 3+ for Nd/Cr:YAG and Cr:YAG ceramic powders in the Cr 3+ concentration range of 0.1–6.0 mol%. The energy transfer process between Cr 3+ and Nd 3+ at the 4 T 1 level excitation is tried to explain using a rate equation that assumes energy transfer from the 2 E – 4 T 2 level to Nd 3+ on the basis of dipole–dipole interactions, the same as the 4 T 2 level excitation. In conclusion, the energy excited to the 4 T 1 level will relax non-radiatively to the 2 E – 4 T 2 level and then transfer to Nd 3+ . It is presumed there will be no direct transfer from the 4 T 1 level to Nd 3+ . Our rate equations will be useful when simultaneously exciting the 4 T 1 and 4 T 2 levels of Cr 3+ in Nd/Cr:YAG using broadband pumping sources.